EFFECT OF HOT PRESSING TEMPERATURE ON THE PERFORMANCE OF PROTON EXCHANGE MEMBRANE FUELCELL BASED ON GAS DIFFUSION ELECTRODE CARBON PAPER AND CARBON CLOTH - Yuyun Irmawati; Indriyati Indriyati; Achiar Oemry (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
EFFECT OF HOT PRESSING TEMPERATURE ON THE PERFORMANCE OF PROTON EXCHANGE MEMBRANE FUELCELL BASED ON GAS DIFFUSION ELECTRODE CARBON PAPER AND CARBON CLOTH. This paper investigates the effect of hot pressing temperature on the performance of Membrane Electrode Assembly (MEA) and to examine the performance differences between Proton Exchange Membrane Fuel Cell (PEMFC) that used Gas Diffusion Electrode (GDE) based on Carbon Cloth (CC) and Carbon Paper (CP). The temperature during hot-pressing was varied of 120 and 150 °C, while the other parameters, such as time and pressure were set steadily at 5 minute and 20 kgf/cm2, respectively. By examining the polarization curves of PEMFC with active area of 50 cm2 at pressure of 1 bar, temperature of 25 °C, and excess gas flow rate of pure H2 and O2, CC was found to have better performance than CP when pressing at 120 °C, while CP has higher performance at 150 oC. Further investigation on activation and ohmic losses using empirical equation revealed that hot pressing temperature just affects the ohmic losses for the CC, while for CP, both activation and ohmic regions considerably changed. The different performances are mainly due to the structural differences such as surface roughness and porosity between CC and CP.Maximum power of 1.53 watt was obtained from GDE based on CC hot pressed at 120 °C, followed by GDE based on CP hot pressed at 150 °C with maximum power of 1.45 watt